Physical-chemical properties of bismuth and bismuth oxides: synthesis, characterization and applications (2012)
The physical-chemical properties of bismuth and its oxides have been studied over the last two decades. As a result of this research, the growth of these materials with different crystallographic structures, showing micro and nanometric dimensions has been achieved by using several techniques (cathodic pulverization, laser pulsed deposition and hydrothermal method, among others). The dimensions reached have enabled thin films, nanotubes, nanospheres and nanowires to be obtained, allowing the developing of devices such as heavy metal detectors, optical filters and magnetic field sensors. Due to the progress in these materials in recent years, in this work a bibliographical review was carried out of some techniques employed for processing bismuth based materials with nanometric dimension and some technological applications.